Cyclophosphamide: An Alternative Treatment in Crohn’s Disease - Gilles Lapointe; Aubin Charbonneau (Canadian Journal of Gastroenterology)
lmmunosuppressive therapy in the form of 6-mercaptopurine has shown a 66% efficacy in severe, debilitating, highly corticosteroid dependent Crohn’s disease. Nevertheless this medication has some important side effects such as nausea, vomiting, leukopenia and pancreatitis. Two patients are presented who, suffering from severe Crohn’s disease, were unable to tolerate 6-mercaptopurine but showed an amazing improvement with cyclophosphamide.